Time reduction with a mini power saw blade in first carpometacarpal Ensemble arthroplasty: a case report - Jay Garvey; Scott Gargasz (Journal of Medical Case Reports)
Abstract Background Shaping the trapezium and metacarpal base during first carpometacarpal (CMC) Ensemble arthroplasty traditionally relies on manual rasping. This is time-consuming and poses the risk of iatrogenic nerve injury due to repeated rasping near the dorsal and volar branches of the dorsal radial sensory nerve. This case report presents a novel modification to the surgical technique by integrating a mini power saw to streamline joint space preparation. Case presentation A 56-year-old Caucasian female patient presented with advanced first carpometacarpal osteoarthritis and chronic pain. She underwent multiple rounds of corticosteroid injections into the first carpometacarpal joint that provided only short-term relief. She expressed her desire for long-term relief and underwent Ensemble arthroplasty at the first carpometacarpal with this modification to the technique. Intraoperative fluoroscopy confirmed optimal implant positioning. The patient began occupational therapy 2 weeks post-surgery, attending sessions two to three times per week. Conclusion This innovative approach reduced operative time by 20 minutes compared to traditional rasping, with postoperative outcomes comparable to those of the standard technique. This report highlights a potential advancement in surgical efficiency and safety.